Expression of long noncoding RNA uc.375 in bronchopulmonary dysplasia and its function in the proliferation and apoptosis of mouse alveolar epithelial cell line MLE 12 - Bao, Tianping; Zhu, Haiyan; Zheng, Yafei; Hu, Jingjing; Wang, Huifang; Cheng, Huaiping; Zhang, Yuan; Tian, Zhaofang (Frontiers in Physiology, 2022)
Background: According to gene ChIP results, long noncoding RNA uc.375 was down-regulated in lung tissue of bronchopulmonary dysplasia (BPD) mice induced by hyperoxia. FoxA1 gene showed higher levels in lung tissue of BPD mice and is reported to promote the apoptosis of alveolar epithelial cells. We aimed to clarify the expression pattern of uc.375 in BPD and explore the interaction between uc.375 and FoxA1. Methods: Newborn mice were placed in a 95% high-oxygen environment for 7 days. Lung tissue samples from mice were used for lncRNA microarray to screen BPD related lncRNAs. Mouse alveolar epithelial cell line MLE12 was stably transfected with uc.375 and FoxA1 silencing or overexpression lentiviral vectors. The proliferation activity of MLE 12 cells was detected by a cell counting kit 8 (CCK-8) assay. MLE12 cell apoptosis was determined by Hoechst/PI staining and flow cytometry analysis. The protein levels of Cleaved-caspase3, FoxA1, SP-C and UCP2 were investigated by western blot. The relative mRNA expression levels were detected by quantitative real-time PCR. Results: uc.375 is mainly distributed in the nucleus of alveolar epithelial cells, as revealed by In Situ Hybridization assay results. uc.375 was lowly expressed in the lung tissues of BPD mice. According to the results of CCK-8 assay, analysis of Hoechst/PI staining and western blotting uc.375 silencing inhibited cell proliferation, facilitated apoptosis of MLE 12 cells, promoted caspase 3 and FoxA1 expression, and inhibited the expression of SP-C and UCP2. On the contrary, after overexpressing uc.375, the opposite results were obtained. Silencing FoxA1 inhibited MLE12 apoptosis, promoted proliferation, inhibited apoptosis-related factor caspase 3, and promoted the expression of SP-C and UCP2. FoxA1 silencing also reversed the effect induced by uc.375 knockdown on the proliferation and apoptosis of MLE 12 cells. Conclusions: Based on the biomedical images-derived analysis results, uc.375 negatively regulates FoxA1 expression, affects alveolar development, and plays an important role in the initiation and progression of BPD, providing a new molecular target for the prevention and treatment of BPD.